Bergey's Manual of Systematics of Archaea and Bacteria 2015
DOI: 10.1002/9781118960608.gbm01198
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus

Abstract: Hae.mo' phi.lus . Gr. n. haima blood; Gr. n. philos lover; M.L masc. Haemophilus blood‐lover. Proteobacteria / Gammaproteobacteria / Pasteurellales / Pasteurellaceae / Haemophilus Minute to medium‐sized coccobacilli or rods , generally less than 1 µm in width and variable in length, sometimes forming threads or filaments and showing marked pleomorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 299 publications
0
5
1
Order By: Relevance
“…We also observed a significant decrease in the genus, Haemophilus, following HVolTr. This finding is in contrast to a recent study that found a significant increase in Haemophilus , which has been associated with several pathogenic bacteria (Kilian, 2015), following an ultra‐marathon event (Grosicki, Durk, & Bagley, 2019). The difference in findings may be the result of the extreme nature of an ultra‐marathon event.…”
Section: Discussioncontrasting
confidence: 99%
“…We also observed a significant decrease in the genus, Haemophilus, following HVolTr. This finding is in contrast to a recent study that found a significant increase in Haemophilus , which has been associated with several pathogenic bacteria (Kilian, 2015), following an ultra‐marathon event (Grosicki, Durk, & Bagley, 2019). The difference in findings may be the result of the extreme nature of an ultra‐marathon event.…”
Section: Discussioncontrasting
confidence: 99%
“…The relative abundance of genera Haemophilus, Neisseria , and Actinomyces increased in response to urea and decrease in response to AHA supplementation. The members of Haemophilus ferment glucose (Kilian, 2015 ), and H . haemolyticus and H .…”
Section: Discussionmentioning
confidence: 99%
“…Haemophilus are Gram-negative coccobacilli that inhabit the upper respiratory tract and are rarely associated with ocular infections [ 202 , 203 ]. Pathogenic strains that cause disease generally enter the upper respiratory tract through droplet inhalation or direct contact [ 204 ].…”
Section: Gram-negative Ocular Pathogensmentioning
confidence: 99%